1999
DOI: 10.1034/j.1399-0012.1999.130305.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of surgical antimicrobial prophylaxis with and without vancomycin in organ transplant patients

Abstract: Vancomycin surgical prophylaxis does not appear to have an effect on VRE colonization or infection, or on rates of infection with gram-positive bacteria. Elimination of vancomycin prophylaxis in renal transplant patients may be a reasonable part of an overall program to limit vancomycin usage, although as a single measure, its impact may be minimal. Vancomycin surgical prophylaxis may be of greater importance in pancreas transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…These data were exclusively for patients who had undergone liver transplantation. We found that pretransplant MRSA carriage in liver transplant recipients (15,19,23 (16,17,27,36) with pertinent data. The Freitas et al (16) study had zero events in both arms and was not pooled.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…These data were exclusively for patients who had undergone liver transplantation. We found that pretransplant MRSA carriage in liver transplant recipients (15,19,23 (16,17,27,36) with pertinent data. The Freitas et al (16) study had zero events in both arms and was not pooled.…”
Section: Resultsmentioning
confidence: 86%
“…Two articles (26,31) included overlapping data with references (15) and (19), leaving a total of 23 studies coded from 25 articles (13 studies reported MRSA colonization data and 11 VRE colonization data) ( Figure 1flow chart). Seventeen out of these 23 studies (74%) enrolled liver transplant patients; 2 studies included kidney transplant recipients (12,16), 2 studies included kidney and/ or pancreas transplant recipients (13,27) and 2 included lung transplant recipients (32,33). All studies used culture methods for MRSA and VRE surveillance and were deemed of adequate quality (see Supplementary Appendix) to extract the main outcome measure, namely the colonization rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…VRE has emerged as an important pathogen in liver, kidney, and SCT units in the United States. [4][5][6][7][8]20 Colonization with VRE has been reported in as many as 50% of pediatric oncology patients. 17 At present, there are very limited data with regard to the incidence and clinical consequences of VRE in pediatric SCT patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Immune compromised patients, especially adult liver, kidney, and pancreatic transplant patients, have experienced serious morbidity and mortality as a consequence of VRE. [4][5][6][7][8] The first reported case of VRE bacteremia in a bone marrow transplant recipient was described in 1991. 9 Recent reports in adult stem cell transplant (SCT) patients have shown that VRE bacteremia results in significant complications and fatalities.…”
mentioning
confidence: 99%